Effect of Adjusted Antiplatelet Therapy on Preventing Ischemic Events After Stenting for Intracranial Aneurysms. Issue 12 (December 2021) - Li, Wenqiang; Zhu, Wei; Wang, Anxin; Zhang, Guojun; Zhang, Yisen; Wang, Kun; Zhang, Ying; Wang, Chao; Zhang, Limin; Zhao, Hui; Wang, Ping; Chen, Kelin; et al.
Abstract : Background and Purpose: This study tests whether patients with unruptured intracranial aneurysm who underwent stent placement benefitted from platelet function monitoring–guided adjustment of antiplatelet therapy. Methods: We conducted a randomized, open-label, parallel group, assessor-blinded trial. Patients with unruptured intracranial aneurysm who underwent stent placement were assigned in a 1:1 ratio to receive either drug adjustment (patients who had high on-treatment platelet reactivity to antiplatelet therapy on the basis of platelet function monitoring [monitoring group]) or conventional therapy (without monitoring and drug adjustment [conventional group]). The second monitoring was performed 14 days after randomization in patients with drug adjustment. The primary outcome was the composite frequency of ischemic stroke, transient ischemic attack, stent thrombosis, urgent revascularization, and cerebrovascular death within 7 days after stent implantation. The safety outcome was the composite frequency of major, minor, or minimal bleeding within 1 month after stent implantation. Results: In total, 314 patients were included (n=157 per group). The primary combined outcome occurred in 19 patients (12.1%) in the conventional group and 8 patients (5.1%) in the monitoring group (hazard ratio, 0.39 [95% CI, 0.17–0.92]; P =0.03). Ischemic stroke occurred at a lower frequency in the monitoring group compared with that in the conventional group (4.5% versus 12.1%; hazard ratio, 0.34 [95% CI, 0.14–0.83]; P =0.01), which drove the overall primary combined outcome. The safety outcome occurred in the monitoring group (7.0%) and in the conventional group (1.9%; hazard ratio, 3.87 [95% CI, 1.06–14.14]; P =0.03). A significant difference was observed in the frequency of minor or minimal bleeding events between the two groups (monitoring group versus conventional group, 6.4% versus 1.3%; P =0.02) but not in the frequency of major bleeding events between the two groups. Conclusions: Platelet function monitoring–guided antiplatelet therapy reduces thromboembolic events in patients with unruptured intracranial aneurysm after stent placement, significantly enhancing minor or minimal bleeding events but not major bleeding events. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03989557. Abstract : Supplemental Digital Content is available in the text.